A wake-up call theory of contagion - Toni Ahnert; Christoph Bertsch (European Central Bank (ECB), 2022)
We offer a theory of financial c ontagion b ased o n t he i nformation c hoice o f i nvestors after observing a financial crisis e lsewhere. We study global coordination games of regime change in two regions linked by an initially unobserved macro shock. A crisis in region 1 is a wake-up call to investors in region 2. It induces them to reassess the regional fundamental and acquire information about the macro shock. Contagion can occur even after investors learn that region 2 has no ex-post exposure to region 1. We explore normative and testable implications of the model. In particular, our results rationalize evidence about contagious currency crises and bank runs after wake-up calls and provide some guidance for future empirical work.
Keywords: D83; F3; G01; G21; 330; wake-up call; information choice; financial crises; contagion; bankrun; global games; fundamental re-assessment